Analysis of The Suitability of Residential Land Around The Balongan Industrial Designation Area - Djatmiko, Ari; Raharja, Apriadi Budi; Fadillah, Muhammad Luthfi (Jurnal Koridor, 2023)
In the analysis of the suitability of residential land locations around the Balongan industrial area, some provisions must be taken into account, one of which is land suitability, where with land suitability analysis, it is possible to determine the level of suitability of residential land that is suitable for use as a residence. To determine the limited level of land suitability by using variables determining land suitability, which includes slope, rainfall, soil texture, and land use. The analysis consisted of 3 (three) stages. The first stage used nearest-neighbor analysis to explain settlement distribution patterns. In the second stage, an analysis of the suitability of residential land was carried out using overlapping techniques related to physical environmental data based on selected variables for residential areas. The third stage is preparing recommendations for residential development locations around the Balongan industrial area with an overlay analysis based on parameters, namely parameters for protected rice fields (LSD), sustainable food agricultural land (LP2B), and the spatial pattern plan for Indramayu Regency for 2011-2031. Based on the analysis, it was concluded that there are three types of settlements around KPI Balongan. The ideal location for residential land to be developed based on land suitability analysis and spatial pattern planning is in Juntikebon Village, Sudimampir Village, with a settlement pattern that can be developed into medium and large types.